Psychometric Properties of the Revised Trolling Questionnaire in Argentinean Adults - Santiago Resett (Acta Colombiana de Psicología, 2023)
Trolling with new technologies is a disruptive, deceptive, and destructive behavior, with great psychosocial, legal, and economical relevance. However, there are no studies in the scientific literature that have examined the properties of questionnaires to assess them. Therefore, the purpose of the present study was to observe the psychometric properties of the Revised Trolling Questionnaire by Buckels et al.'s in a sample of Argentinean adults. An intentional sample of 837 participants from Argentina (mean age = 28.4 years; 61% female) was formed. They completed the Buckels et al.'s Revised Trolling Questionnaire, measures of dark personality, Internet addiction, cyberstalking, and socio-demographic questions. Exploratory and confirmatory factorial analyses indicated a one-factor structure with correct fit statistics. Internal consistency was adequate: Cronbach's α = .80 and Omega coefficient (ω) = .81. Concurrent validity of the trolling questionnaire was observed with dark personality (Machiavellianism, narcissism and psychopathy), problematic Internet use (symptomatology and disfunctionality), and cyberstalking. Machiavellianism and disfunctionality were the most significant variables associated with trolling. Therefore, the Argentinean Spanish version of this test showed evidence of adequate psychometric properties.